The Best Adders of Opportunity Government Skills Initiatives in the United Kingdom - J. Simmons (University of Sofia, 2010)
The focus of this paper is United Kingdom (UK) govern¬ment initiatives over the last thirty years, or so, which have been designed to both up-skill the workforce and to improve the country's international com¬petitive position. It also considers the impact which these educational inter¬ventions have had on the economic and human capital of the various stake¬holders including the government, employers and learners. It comes to the conclusion that, whilst some progress has been made in developing the human capital and the economic capital of the stakeholders these interventions have not significantly improved the United Kingdom's global competitive position. The paper also points to the current political uncertainty in that country.